Symplectic Applicability of Lagrangian Surfaces - Musso, E.; Nicolodi, L. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
We develop an approach to affine symplectic invariant geometry of Lagrangian surfaces by the method of moving frames. The fundamental invariants of elliptic Lagrangian immersions in affine symplectic four-space are derived together with their integrability equations. The invariant setup is applied to discuss the question of symplectic applicability for elliptic Lagrangian immersions. Explicit examples are considered.